2019
DOI: 10.1097/scs.0000000000004900
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Compliance of Randomized Controlled Trials Published in Craniofacial Surgery Journals With the CONSORT Statement

Abstract: Background: Randomized controlled trials (RCTs) are gold standard assessments for healthcare interventions. The Consolidated Standards of Reporting Trials (CONSORT) statement was published to maximize RCT reporting transparency. The authors conducted a systematic review to assess current compliance of RCTs published within craniofacial surgery with the CONSORT statement. Methods: The Thomson Reuters Impact Factor Report 2016 was consulted to identify cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Lack of adherence to guidelines has been widely reported in the literature. 13,14,21,22 Journal committees, such as the International Committee of Medical Journal Editors (ICMJE), could act as a catalyst to improving the quality of reporting of large database studies by encouraging/requiring member journals to implement and enforce reporting statement policies. Additionally, further efforts should focus on incorporating reporting standards in research training, including a checklist for authors as part of the submission process, and assessing adherence to guidelines as a requirement of peer review to mitigate the risk of bias from under-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of adherence to guidelines has been widely reported in the literature. 13,14,21,22 Journal committees, such as the International Committee of Medical Journal Editors (ICMJE), could act as a catalyst to improving the quality of reporting of large database studies by encouraging/requiring member journals to implement and enforce reporting statement policies. Additionally, further efforts should focus on incorporating reporting standards in research training, including a checklist for authors as part of the submission process, and assessing adherence to guidelines as a requirement of peer review to mitigate the risk of bias from under-reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional or retrospective systematic surveys have been done in dentistry to assess compliance with the CONSORT statement [ 40 45 ]. Consistent with our findings, none of them reports optimal compliance.…”
Section: Discussionmentioning
confidence: 99%
“…While practically none of the journals in our study have an impact factor, our findings are consistent with this study because one of the items most frequently reported was a structured abstract, albeit with only 70% compliance. Borrelli et al used the impact factor report for 2016 to identify craniofacial surgery journals and assess RCT compliance with the CONSORT statement [ 45 ]. Like the previous study that only included journals with an impact factor, this study also found compliance with CONSORT to be 56% (minimum 33%, maximum 94%) of applicable items reported.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Consolidated standards of reporting trial flow chart should appear in the methods section for any RCT. [3]…”
Section: Methodsmentioning
confidence: 99%